Quantum magnetism - Schollwock, Ulrich (Springer, 2015)
Surveys conceptual problems and provide insights into the classes of systems considered, namely one-dimensional, two-dimensional, and molecular magnets. This title introduces the methods used in the field of quantum magnetism, including spin wave analysis, exact diagonalization, quantum field theory, coupled cluster methods, and the Betheansatz.